Analisis Stretagi Pekerja Migran Indonesia dalam Menyikapi Kontrak Kerja - Santoso, Rio (Jurnal Ekonomi & Bisnis, 2024)
Indonesian Migrant Workers (PMI) Government to Government (G to G) process are faced with various challenges who work in South Korea through the South Korean, especially those related to work contract standards. PMI who are placed in workplaces in the manufacturing sector for E-9 visas and fishing for E-10 visas with a maximum work contract period of 4 years and 10 months during the first work contract period. PMI's standard work contract in South Korea through the Government to Government (G to G) program contains the rights and obligations of workers and employers. This research aims to provide an understanding of PMI's strategy in responding to employment contracts in South Korea. The subjects of this research were 48 Indonesian Migrant Workers in South Korea who had just worked in South Korea or who had worked by re-entry (entering work back into South Korea on a second contract). The type of data used is quantitative data, primary data collected through questionnaires with PMI who are working in South Korea, secondary data obtained through relevant literature studies. The data analysis technique uses qualitative descriptive analysis. The research results show that: 1) effective communication with other people, migrant workers need to have good interpersonal communication skills, both with colleagues and superiors, 2) the importance of migrant workers having knowledge about their rights, work regulations, working conditions in Korea South, 3) migrant workers need knowledge and skills to recognize and deal with discrimination by adapting according to local culture and work environment, 4) skills can include language, technical and social skills to improve job opportunities even better.